A heat-conducting gel with high damping and high resilience performance and a preparation method thereof

CN116875059BActive Publication Date: 2026-10-27SHENZHEN INST OF ADVANCED ELECTRONICS MATERIALS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310956443.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2026-10-27
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

上述工作所涉及的通过连续的动态键断裂-重组有效地耗散冲击能对设计具有高阻尼性能的导热凝胶具有启示作用,但是梳状共聚物/悬挂链极易在外力作用下发生滑移等不可回复,导致导热凝胶回弹性能变差的潜在问题

Benefits of technology

[0060](1)高填充量的导热凝胶中,聚合物-填料界面分子链是聚合物基体的重要组成部分,也是影响导热凝胶阻尼性能和回弹性能的关键因素。本发明从聚合物-填料界面结构设计出发,通过有机硅基体和填料表面的化学性质调控实现界面缠结的“滑轮效应”,其对优异的阻尼性能和回弹性能的实现起到了重要作用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116875059B_ABST
    Figure CN116875059B_ABST
Patent Text Reader

Abstract

The application discloses a heat-conducting gel with high damping and high resilience, and comprises, in terms of weight parts, side-chain vinyl silicone oil 1-70 parts, double-end hydrogen-containing silicone oil 0.1-20 parts, side-chain hydrogen-containing silicone oil 0.01-5 parts, single-end hydrogen-containing silicone oil 1-10 parts, a catalyst 0.01-1.0 parts, an inhibitor 0.005-0.5 parts, modified heat-conducting fillers 60-95 parts, wherein the modified heat-conducting fillers are heat-conducting fillers modified by a silane coupling agent, the mass of the silane coupling agent is 0.1%-1.5% of the mass of the heat-conducting fillers, and the hydrogen content of the single-end hydrogen-containing silicone oil is 0.01%-0.12%. The application realizes the 'pulley effect' of interface entanglement by regulating the chemical properties of the silicone matrix and the filler surface based on the polymer-filler interface structure, dissipates energy through molecular chain sliding friction, and maintains resilience through molecular chain mechanical interlocking, so that the heat-conducting gel has high damping, high resilience and high heat conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermal interface materials technology, and in particular to a thermally conductive gel with both high damping and high resilience properties, and its preparation method. Background Technology

[0002] The operating conditions of power electronic devices are becoming increasingly demanding, including extreme high-temperature environments, large alternating temperature difference stress shocks, and mechanical vibrations caused by the application environment during vehicle operation. Statistics from the U.S. Air Force Aeronautical Electronics Analysis Center show that electronic device failures caused by excessive temperature and vibration account for up to 75%. In chip packaging structures, silicone thermal conductive gels are typically used to fill the air gap between the chip and the heat sink, establishing an effective heat conduction channel to ensure the stability and reliability of chip operation. However, vibration, temperature, and other factors can cause the thermal conductive gel to slip or pump out, leading to thermal control failures and engineering failures in electronic devices. Therefore, developing silicone thermal conductive gels with high damping, high resilience, and high thermal conductivity is not only an important means of strengthening the barrier protecting chips from external damage but also ensuring an effective heat conduction channel.

[0003] Adding high-filler thermally conductive fillers is an important means to achieve high thermal conductivity in thermally conductive gels, but it will severely sacrifice damping performance. Introducing hanging chains and interpenetrating polymer network structures into the system can improve the material's damping performance, but it will sacrifice rebound performance. For thermally conductive gels with high filler content, the polymer-filler interface molecular chain is an important component of the polymer component in the thermally conductive gel and a key factor affecting the damping and rebound performance of the thermally conductive gel. Chinese invention patent CN202111169750.8, in order to solve the problem of electronic instruments and equipment failure due to collisions and drops, developed a thermally conductive gel with good adhesion and drop resistance. It introduces an epoxy-containing organosilicon anchoring agent into the system to enhance the adhesion between the thermally conductive gel and the chip, but its thermal conductivity is only about 3 W / (m·K). Chinese invention patent CN114163818A, drawing inspiration from the bristle structure of a gecko's toes, utilizes the brush-like molecular chain side chain structure in the polymer matrix to capture fillers and rough surface defects of the substrate, thus preparing an organosilicon thermally conductive gel with high thermal conductivity, low contact thermal resistance, and excellent damping function. Similarly, Chinese invention patent CN202210170545.1 discloses a scheme based on the classic Maxwell model, introducing a large number of short suspended chain structures into the organosilicon system to prepare a broadband, wide-range, high-damping thermally conductive gel. The above-mentioned work, which effectively dissipates impact energy through continuous dynamic bond breaking and recombination, is inspiring for the design of thermally conductive gels with high damping performance. However, the comb-like copolymer / suspended chain is prone to slippage and other irreversible phenomena under external forces, leading to a potential problem of poor resilience of the thermally conductive gel. To address the issue of declining mechanical properties and reliability caused by the inability of thermally conductive gels to recover their original state after long-term use, Chinese invention patent CN202111453625.X reported a scheme for preparing low-hysteresis thermally conductive gels by replacing freely moving silicone oil in the system with the physical entanglement and interaction of polymer molecular chains, providing a new approach for the design of high-resilience thermally conductive gels. However, this invention overlooks the barrier function of thermally conductive gels in protecting chips from external damage. Therefore, research on organosilicon-based thermally conductive gels that combine high damping, high resilience, and high thermal conductivity is of practical significance. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a thermally conductive gel with both high damping and high resilience properties, as well as its preparation method. Starting from the polymer-filler interface structure design, this invention achieves a "pulley effect" of interfacial entanglement through the chemical property control of the organosilicon matrix and filler surface. This effect allows energy to dissipate through sliding friction of molecular chains and maintains resilience through mechanical interlocking of molecular chains, thereby achieving high damping, high resilience, and high thermal conductivity in the organosilicon thermally conductive gel.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] On one hand, the present invention provides a thermally conductive gel with both high damping and high resilience properties, comprising, by weight:

[0007] (1) Side-chain vinyl silicone oil, 1-70 parts;

[0008] (2) 0.1 to 20 parts of double-ended hydrogen-containing silicone oil;

[0009] (3) 0.01 to 5 parts of hydrogen-containing silicone oil in the side chain;

[0010] (4) 1-10 parts of single-ended hydrogen-containing silicone oil;

[0011] (5) Catalyst 0.01–1.0 parts;

[0012] (6) Inhibitor 0.005–0.5 parts;

[0013] (7) 60-95 parts of modified thermally conductive filler;

[0014] The modified thermally conductive filler is a thermally conductive filler modified by a silane coupling agent; the mass of the silane coupling agent is 0.1% to 1.5% of the mass of the thermally conductive filler; the hydrogen content of the single-ended hydrogen-containing silicone oil is 0.01% to 0.12%.

[0015] In the technical solution of the present invention, the molecular weight of the single-ended hydrogen-containing silicone oil is negatively correlated with the hydrogen content. Generally, the reciprocal of the hydrogen content can be considered as the molecular weight, which is about 800g / mol to 10000g / mol.

[0016] For thermally conductive gels with high filler content, the polymer-filler interface molecular chain is an important component of the polymer component in the thermally conductive gel and a key factor affecting the damping and resilience properties of the thermally conductive gel. This invention achieves an interfacial pulley effect through the synergistic effect of a suspended chain structure mainly composed of single-ended hydrogen-containing silicone oil and a silane coupling agent, overcoming the limitations of existing designs that utilize suspended chain structures to reduce crosslinking density and prevent oil seepage, and silane coupling agents to improve interfacial compatibility. When the molecular weight of the suspended chain structure mainly composed of single-ended hydrogen-containing silicone oil is too low, its improvement of interfacial adhesion relies solely on adsorption (Chinese Invention Patent CN114163818A), failing to form effective interfacial entanglement. When the molecular weight is too high, it will form a "quasi-crosslinking" physical entanglement instead of dissipating energy through molecular chain sliding friction, sacrificing the damping properties of the thermally conductive gel and even affecting its tensile properties. Furthermore, low-molecular-weight silane coupling agents cannot form effective physical entanglement with the organosilicon matrix. High molecular weight silane coupling agents not only affect the modification and grafting effect but also inevitably introduce solvents. Therefore, by controlling the chemical properties of the organosilicon matrix and filler surface, and utilizing the "pulley effect" of interfacial entanglement achieved by the suspended chain structure in the organosilicon matrix and the silane coupling agent on the filler surface, energy can be dissipated through sliding friction of molecular chains, and elasticity can be maintained through mechanical interlocking of molecular chains, thereby achieving high damping and high elasticity of organosilicon thermal conductive gels.

[0017] In some specific embodiments, the vinyl content in the side-chain vinyl silicone oil is 0.1% to 1.0%; the hydrogen content in the double-ended hydrogen-containing silicone oil is 0.01% to 0.3%; and the hydrogen content in the side-chain hydrogen-containing silicone oil is 0.05% to 0.7%.

[0018] In some specific embodiments, the side-chain vinyl silicone oil is expressed in parts by weight of 1 part, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, or any number of parts by weight therein.

[0019] In some specific embodiments, the weight parts of the double-ended hydrogen-containing silicone oil are 0.1 parts, 1 part, 4 parts, 6 parts, 8 parts, 10 parts, 15 parts, 20 parts, or any weight parts thereof.

[0020] In some specific embodiments, the side-chain hydrogen-containing silicone oil is in the following weight proportions: 1 part, 2 parts, 3 parts, 4 parts, 5 parts, or any weight proportions thereof.

[0021] In some specific embodiments, the single-ended hydrogen-containing silicone oil is 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 1 part or any number of parts by weight therein.

[0022] In some specific embodiments, the modified thermally conductive filler is 60 parts, 70 parts, 80 parts, 90 parts, 95 parts by weight or any number of parts by weight therebetween.

[0023] In a preferred embodiment, the thermally conductive gel comprises, by weight:

[0024] (1) 6-10 parts of side-chain vinyl silicone oil;

[0025] (2) 0.1 to 1 part of double-ended hydrogen-containing silicone oil;

[0026] (3) 0.01 to 0.03 parts of hydrogen-containing silicone oil in the side chain;

[0027] (4) 1-4 parts of single-ended hydrogen-containing silicone oil;

[0028] (5) Catalyst 0.01–1.0 parts;

[0029] (6) Inhibitor 0.005–0.5 parts;

[0030] (7) 60-95 parts of modified thermally conductive filler.

[0031] In a preferred embodiment, the silane coupling agent is selected from at least one of 3-(polysiloxane)propyltrimethoxysilane of formula (1) and alkyltrimethoxysilane of formula (2);

[0032]

[0033] In equation (1), n ​​= 1 to 10;

[0034] In some specific embodiments, the molecular weight of 3-(polysiloxane)propyltrimethoxysilane as shown in formula (1) is 400 g / mol to 1000 g / mol;

[0035]

[0036] In equation (2), m = 8 to 16;

[0037] In some specific embodiments, the molecular weight of the alkyltrimethoxysilane shown in formula (2) is 260 g / mol to 400 g / mol.

[0038] In some specific embodiments, the alkyltrimethoxysilanes shown in formula (2) may include octadecyltrimethoxysilane, hexadecyltrimethoxysilane, dodecyltrimethoxysilane and decyltrimethoxysilane, etc., which can be used alone or in any combination.

[0039] In a preferred embodiment, the preparation method of the modified thermally conductive filler includes the following steps:

[0040] The modified thermally conductive filler is obtained by dispersing the thermally conductive filler in a hydrolysate containing the silane coupling agent and stirring the reaction solution.

[0041] Preferably, the stirring reaction is carried out at room temperature for 0.5 to 2 hours, followed by a reaction at 100 to 150°C for 0.5 to 2 hours; in the technical solution of the present invention, room temperature refers to a temperature at which no additional heating operation is required.

[0042] Preferably, the hydrolysate containing the silane coupling agent is a mixed solution containing the silane coupling agent, a first solvent, and a second solvent; the first solvent is selected from at least one of water and toluene; and the second solvent is selected from at least one of ethanol and methanol.

[0043] Preferably, the mass ratio of the silane coupling agent, the first solvent, and the second solvent is 1:0.5 to 2:1 to 5;

[0044] Preferably, the method for preparing the hydrolysate containing the silane coupling agent includes mixing and stirring the silane coupling agent, a first solvent, and a second solvent until the solution becomes clear.

[0045] In a preferred embodiment, the catalyst is selected from at least one of chloroplatinic acid, chloroplatinic acid-isopropanol complex, and chloroplatinic acid-divinyltetramethyldisiloxane complex.

[0046] In a preferred embodiment, the inhibitor is selected from at least one of ethynylcyclohexanol, 2-phenyl-3-butyn-2-ol, 2-methyl-3-butyn-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-ethynyl-3-ol, and 3-methyl-1-dodecynyl-3-ol.

[0047] In a preferred embodiment, the thermally conductive filler is selected from at least one of alumina, aluminum, zinc oxide, aluminum hydroxide, and magnesium hydroxide;

[0048] Preferably, the particle size of the thermally conductive filler is 0.1–100 μm;

[0049] Preferably, the thermally conductive filler is formulated in a mass ratio of 40-60:40-60:1-30, with a particle size of 80-100μm: 20-50μm: 0.1-10μm.

[0050] In another aspect, the present invention provides a method for preparing the above-mentioned thermally conductive gel, comprising the following steps:

[0051] (1) Stir the side-chain vinyl silicone oil, double-ended hydrogen-containing silicone oil, side-chain hydrogen-containing silicone oil, single-ended hydrogen-containing silicone oil, inhibitor and modified thermally conductive filler.

[0052] (2) After adding the catalyst, continue stirring to obtain the thermally conductive gel.

[0053] In a preferred embodiment, the stirring in step (1) is carried out under vacuum conditions;

[0054] Preferably, the vacuum degree is not lower than -90.0 kPa;

[0055] Preferably, the stirring speed is 50-100 rpm, and the stirring time is 1-3 hours.

[0056] In a preferred embodiment, in step (2), the continued stirring is carried out under vacuum conditions;

[0057] Preferably, the vacuum degree is not lower than -90.0 kPa;

[0058] Preferably, the stirring speed is 50-100 rpm and the stirring time is 1-3 hours.

[0059] The above technical solution has the following advantages or beneficial effects:

[0060] (1) In thermally conductive gels with high filler content, the polymer-filler interface molecular chains are an important component of the polymer matrix and a key factor affecting the damping and rebound performance of the thermally conductive gel. This invention starts from the design of the polymer-filler interface structure and achieves the "pulley effect" of interfacial entanglement by regulating the chemical properties of the organosilicon matrix and the filler surface. This plays an important role in achieving excellent damping and rebound performance.

[0061] (2) This invention achieves the “pulley effect” of interfacial entanglement for the first time by regulating the suspended chain structure in the organosilicon matrix and the silane coupling agent structure on the filler surface. Under the synergistic effect of the two, energy can be dissipated through the sliding friction of molecular chains, and the elasticity can be maintained through the mechanical interlocking of molecular chains.

[0062] (3) The organosilicon thermally conductive gel prepared by this invention has excellent damping performance, resilience performance and high thermal conductivity. On the one hand, the polymer-filler interface molecular chains dissipate energy through sliding friction, achieving high damping performance (tanδ>0.3) over a wide frequency range (0.1Hz to >100Hz); on the other hand, the polymer-filler interface molecular chains can still maintain an entangled state—mechanical interlocking effect, which endows the thermally conductive gel with high resilience (>80%) and low permanent deformation (<20%); finally, the high thermal conductivity can be achieved by controlling the filling amount of thermally conductive filler, etc., with a thermal conductivity of 3.0 to 10 W / (m·K).

[0063] (4) The thermally conductive gel prepared by this invention, which combines high damping and high resilience, has a significant advantage in ensuring the bonding between the thermally conductive gel and the substrate / chip interface. The copper plate-thermally conductive gel-copper plate sandwich structure laminate prepared by it still has an interface bonding area of ​​84% after 40 compression-recovery cycles under a large strain of 20%, which will effectively ensure the heat dissipation effect of the system and has great application potential. Attached Figure Description

[0064] Figure 1 This is a schematic diagram of the modification process of the thermally conductive filler in the embodiments and comparative examples of the present invention;

[0065] Figure 2 This is a schematic diagram of the "pulley effect" principle of the thermally conductive gel interface in an embodiment of the present invention;

[0066] Figure 3 These are ultrasonic microscopic images of the copper plate-thermal conductive gel-copper plate sandwich structure laminate prepared in Example 1 of the present invention before and after compression and rebound.

[0067] Figure 4 The image shows ultrasonic microscopic images of the copper plate-thermal conductive gel-copper plate sandwich structure laminate prepared by the thermal conductive gel in Comparative Example 1 of the present invention before and after compression and rebound.

[0068] Figure 5 The images are ultrasonic micrographs of the copper plate-thermal conductive gel-copper plate sandwich structure laminate prepared by the thermal conductive gel in Comparative Example 2 of the present invention before and after compression and rebound. Detailed Implementation

[0069] The following embodiments are only some, not all, of the embodiments of the present invention. Therefore, the detailed descriptions of the embodiments provided below are not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0070] In this invention, unless otherwise specified, all equipment and raw materials are commercially available or commonly used in the industry. The methods described in the following embodiments are conventional methods in the art, unless otherwise specified.

[0071] Example 1

[0072] The preparation method of the thermally conductive gel in this embodiment includes the following steps:

[0073] (1) Preparation of silane coupling agent hydrolysate: Dodecyltrimethoxysilane, deionized water and anhydrous methanol are mixed and stirred at 200 rpm at room temperature for 30 minutes in a mass ratio of 1:1:3. The solution is ready for use when it changes from turbid to clear.

[0074] (2) Preparation of modified thermally conductive filler: Alumina with a particle size of 100 μm, alumina with a particle size of 50 μm, and zinc oxide with a particle size of 0.3 μm were added to a planetary mixer in a mass ratio of 47:47:6 and stirred. After 10 min, the prepared silane coupling agent hydrolysate was added to the above filler, wherein the amount of silane coupling agent was 0.5% of the total mass of the filler. After stirring at room temperature for 1 hour, the planetary mixer cavity was heated to 120°C and the vacuum valve was opened to evacuate the vacuum. Stirring was continued for 1 hour. Finally, after cooling to room temperature, the modified thermally conductive filler was obtained.

[0075] (3) The viscosity is 50 mm 2 / S, Side-chain vinyl silicone oil (14.988g) with a vinyl content of 0.2056% and a viscosity of 70mm 2 / S, Single-ended hydrogen-containing silicone oil with a hydrogen content of 0.02% (molecular weight 5000 g / mol, 8.6693 g), viscosity 340 mm. 2 / S, 0.3041g of double-ended hydrogen-containing silicone oil with a hydrogen content of 0.02% and a viscosity of 105 mm. 2 / S, 0.03852g of side-chain hydrogen-containing silicone oil with a hydrogen content of 0.1%, 216g of modified thermally conductive filler, and 0.02g of ethynylcyclohexanol were added to a 2.0L double planetary mixer and stirred at 50rpm for 2.0h under a vacuum of -90.0kPa.

[0076] (4) Add chloroplatinic acid-divinyltetramethyldisiloxane complex (0.05 g), and continue stirring at 100 rpm for 2.0 h under vacuum of -90.0 kPa to obtain thermally conductive gel.

[0077] In this embodiment, the modification process in step (2) is as follows: Figure 1 As shown, a silane coupling agent is grafted onto the surface of the filler.

[0078] Example 2

[0079] The preparation method of the thermal conductive gel in this embodiment is the same as that in Example 1. The difference is that the preparation method of the silane coupling agent hydrolysate in step (1) is different, as follows: 3-(polysiloxane)propyltrimethoxysilane (chemical structure as shown in formula (3): n=3, molecular weight about 500g / mol) is mixed with deionized water and anhydrous methanol at a mass ratio of 1:1:3 at room temperature and stirred at a speed of 200 rpm for 30 minutes until the solution changes from turbid to clear.

[0080]

[0081] Example 3

[0082] The preparation method of the thermally conductive gel in this embodiment includes the following steps:

[0083] (1) Preparation of silane coupling agent hydrolysate: 3-(polysiloxane)propyltrimethoxysilane (chemical structure as shown in formula (3) above: n=3, molecular weight about 500g / mol) is mixed with deionized water and anhydrous methanol at a mass ratio of 1:1:3 at room temperature and stirred at a speed of 200 rpm for 30 minutes. The solution is ready for use when it changes from turbid to clear.

[0084] (2) Preparation of modified thermally conductive filler powder: Alumina with a particle size of 100 μm, alumina with a particle size of 50 μm and zinc oxide with a particle size of 0.3 μm were added to a planetary mixer in a mass ratio of 47:47:6 and stirred. After 10 min, the prepared silane coupling agent hydrolysate was added to the above filler, wherein the amount of silane coupling agent was 0.5% of the total mass of the filler. After stirring at room temperature for 1 hour, the planetary mixer cavity was heated to 120℃ and the vacuum was turned on, and stirring was continued for 1 hour. Finally, after cooling to room temperature, the modified thermally conductive filler was obtained.

[0085] (3) The viscosity is 50 mm 2 / S, Side-chain vinyl silicone oil (20.9914g) with a vinyl content of 0.2056% and a viscosity of 20mm 2 / S, a single-ended hydrogen-containing silicone oil with a hydrogen content of 0.1176% (molecular weight approximately 850 g / mol, 2.5288 g), and a viscosity of 340 mm. 2 / S, 0.4259g of double-ended hydrogen-containing silicone oil with a hydrogen content of 0.02% and a viscosity of 105 mm. 2 / S, 0.05395g of hydrogen-containing side-chain silicone oil with a hydrogen content of 0.1%, 216g of modified thermally conductive filler, and 0.02g of ethynylcyclohexanol were added to a 2.0L double planetary mixer; and stirred at 50rpm for 2.0h under a vacuum of -90.0kPa.

[0086] (4) Add chloroplatinic acid-divinyltetramethyldisiloxane complex (0.05 g), and continue stirring at 100 rpm for 2.0 h under vacuum of -90.0 kPa to obtain thermally conductive gel.

[0087] Example 4

[0088] The preparation method of the thermal conductive gel in this embodiment is the same as that in Example 1. The difference is that the preparation method of the silane coupling agent hydrolysate in step (1) is different, as follows: 3-(polysiloxane)propyltrimethoxysilane (chemical structure as shown in formula (3) above: n=6, molecular weight about 1000g / mol) is mixed with toluene and anhydrous methanol at a mass ratio of 1:1:3 at room temperature and stirred at a speed of 200 rpm for 30 minutes until the solution changes from turbid to clear.

[0089] Example 5

[0090] The preparation method of the thermally conductive gel in this embodiment is the same as in Example 1, except that the mass of the modified thermally conductive filler is replaced by 219g instead of 216g.

[0091] like Figure 2 As shown, the thermally conductive gel provided by this invention starts from the polymer-filler interface structure design and achieves the "pulley effect" of interface entanglement by regulating the chemical properties of the organosilicon matrix and the filler surface: on the one hand, the polymer-filler interface molecular chains dissipate energy through sliding friction, achieving high damping performance over a wide frequency range; on the other hand, the polymer-filler interface molecular chains can still maintain an entangled state—mechanical interlocking effect—maintaining the high resilience of the thermally conductive gel.

[0092] Comparative Example 1

[0093] The preparation method of the thermally conductive gel in this comparative example includes the following steps:

[0094] (1) The viscosity is 50 mm 2 / S, Side-chain vinyl silicone oil (14.988g) with a vinyl content of 0.2056% and a viscosity of 70mm 2 / S, Single-ended hydrogen-containing silicone oil with a hydrogen content of 0.02% (molecular weight 5000 g / mol, 8.6693 g), viscosity 340 mm. 2 / S, 0.3041g of double-ended hydrogen-containing silicone oil with a hydrogen content of 0.02% and a viscosity of 105 mm. 2 / S, 0.03852g of side-chain hydrogen-containing silicone oil with a hydrogen content of 0.1%, 102.3g of alumina with a particle size of 100μm, 102.3g of aluminum with a particle size of 50μm, 11.4g of zinc oxide with a particle size of 0.3μm, and 0.02g of ethynylcyclohexanol were added to a 2.0L double planetary mixer; and stirred at 50rpm for 2.0h under a vacuum of -90.0kPa.

[0095] (2) Add chloroplatinic acid-divinyltetramethyldisiloxane complex (0.05 g), and continue stirring at 100 rpm for 2.0 h under vacuum of -90.0 kPa to obtain thermally conductive gel.

[0096] Comparative Example 2

[0097] The preparation method of the thermally conductive gel in this comparative example includes the following steps:

[0098] (1) Preparation of silane coupling agent hydrolysate: 3-(polysiloxane)propyltrimethoxysilane (chemical structure as shown in formula (3) above: n=3, molecular weight about 500g / mol) is mixed with deionized water and anhydrous methanol at a mass ratio of 1:1:3 at room temperature at a speed of 200 rpm for about 30 minutes. The solution is ready for use when it changes from turbid to clear.

[0099] (2) Preparation of modified thermally conductive filler: Alumina with a particle size of 100 μm, alumina with a particle size of 50 μm, and zinc oxide with a particle size of 0.3 μm were added to the planetary machine in a mass ratio of 47:47:6 and stirred. After 10 min, the prepared silane coupling agent hydrolysate was added to the above filler, wherein the amount of silane coupling agent was 0.5% of the total mass of the filler. After stirring at room temperature for 1 hour, the planetary machine cavity was heated to 120℃ and the vacuum was turned on, and stirring was continued for 1 hour. Finally, the modified thermally conductive filler was obtained by cooling to room temperature.

[0100] (3) The viscosity is 50 mm 2 / S, 19.5344g of side-chain vinyl silicone oil with a vinyl content of 0.2056% and a viscosity of 340mm. 2 / S, 3.9636g of double-ended hydrogen-containing silicone oil with a hydrogen content of 0.02% and a viscosity of 105mm 2 / S, 0.5020g of side-chain hydrogen-containing silicone oil with a hydrogen content of 0.1%, 216g of modified filler and 0.01g of ethynylcyclohexanol were added to a 2.0L double planetary mixer and stirred at 50rpm for 2.0h under a vacuum of -90.0kPa.

[0101] (4) Add 0.05 g of chloroplatinic acid-divinyltetramethyldisiloxane complex and stir at 100 rpm for 2.0 h under vacuum of -90.0 kPa to obtain thermally conductive gel.

[0102] Comparative Example 3

[0103] The preparation method of the thermal conductive gel in this embodiment is the same as that in Embodiment 3, except that the components of the thermal conductive gel in step (3) are different, as follows:

[0104] (3) The viscosity is 50 mm 2 / S, Side-chain vinyl silicone oil (0.5672g) with a vinyl content of 0.2056% and a viscosity of 15mm 2 / S, a single-ended hydrogen-containing silicone oil with a hydrogen content of 0.2% (molecular weight approximately 5000 g / mol, 23.96 g), viscosity 340 mm. 2 / S, 0.01151g of double-ended hydrogen-containing silicone oil with a hydrogen content of 0.02% and a viscosity of 105 mm. 2 / S, 0.001458g of side-chain hydrogen-containing silicone oil with a hydrogen content of 0.1%, 216g of modified thermally conductive filler, and 0.02g of ethynylcyclohexanol were added to a 2.0L double planetary mixer and stirred at 50rpm for 2.0h under a vacuum of -90.0kPa.

[0105] Comparative Example 4

[0106] The preparation method of the thermally conductive gel in this embodiment is the same as in Example 3, except that the amount of silane coupling agent is adjusted from 0.5% of the total mass of the thermally conductive filler to 2% of the total mass of the thermally conductive filler.

[0107] Performance testing:

[0108] (1) Thermal conductivity test:

[0109] In this embodiment, the thermal conductivity in the vertical direction is determined using the steady-state method standard test method, and the testing instrument is the LW-9389TIM resistivity and conductivity meter.

[0110] (2) Damping performance

[0111] The damping performance of the samples was studied using an Antonpah MCR302 dynamic thermomechanical analyzer from Austria. The test conditions and parameters were as follows: temperature 25℃, test frequency 0.01~100Hz, and amplitude 1%.

[0112] (3) Rebound performance

[0113] At room temperature, the thermally conductive gel was stretched to 60% strain using a precision electronic universal testing machine (model AGX-1kNVD), and the actual strain value ε0 was obtained. Subsequently, the external force was removed, and the stress-strain curve was recorded to obtain the permanent deformation ε1. The loading and unloading rates of the samples were both 3 mm / min. Each sample underwent at least 5 parallel tests. The resilience of the thermally conductive gel was defined as: R = (ε0 - ε1) / ε0.

[0114] (4) Oil seepage rate test

[0115] The oil penetration rate test was conducted according to ASTM C772 standard: the prepared thermally conductive gel was placed on a Whatman sheet and a filter paper. The initial mass m0 of the silicone thermally conductive gel and the weight m1 after 3 days were recorded. The oil penetration rate was defined as k = (m0 - m1) / m0.

[0116] The thermal conductivity, resilience, tanδ value in the frequency range [0.01Hz, >100Hz], and oil penetration rate of the thermally conductive gels prepared in Examples 1-5 and Comparative Examples 1-3 were tested according to the above method, as shown in Table 1. From the resilience performance in Table 1, compared to the thermally conductive gels in Comparative Examples 2 and 3, Examples 1, 2, and 4 demonstrate that the resilience and damping properties of the thermally conductive gels can be controlled by adjusting the suspended chain structure in the silicone matrix and the molecular weight of the silane coupling agent on the surface of the thermally conductive filler. In particular, Example 1 further illustrates the necessity of the synergistic effect of the suspended chain structure in the silicone matrix and the silane coupling agent on the surface of the thermally conductive filler for achieving high tensile and high resilience performance (the thermally conductive gel in Comparative Example 1 could not be stretched to the set strain, and its elongation at break was <60%). Furthermore, the thermally conductive gel in Example 5 exhibits a high thermal conductivity based on the "pulley effect" of polymer / filler interfacial entanglement.

[0117] When the molecular weight of the silane coupling agent is low (Example 1 < Example 2 < Example 4 < Comparative Example 1), effective interfacial physical entanglement cannot be formed. The introduction of short silane coupling agent polymer chains will lead to irreversible energy loss such as slippage, i.e., the resilience performance will deteriorate significantly. It should be noted that the introduction of excessive silane coupling agent will lead to a decrease in thermal conductivity and the risk of oil leakage due to incomplete reaction (Comparative Example 3).

[0118] When the molecular weight of the suspended chain structure is low (Comparative Example 2 < Example 2 < Example 3 < Comparative Example 2), the short silane coupling agent polymer chain and the short suspended chain structure will lead to irreversible energy loss such as slippage, which will significantly deteriorate the resilience performance.

[0119] The function of the single-ended hydrogen-containing silicone oil in this invention differs from the function of reducing the physical entanglement and interaction of polymer molecular chains and reducing spillover disclosed in Chinese invention patent CN113527893A: This invention regulates the chemical properties of the organosilicon matrix and filler surface by controlling the molecular weight and hydrogen content of the single-ended hydrogen-containing silicone oil. The "pulley effect" of interfacial entanglement is achieved through the suspended chain structure mainly formed by the single-ended hydrogen-containing silicone oil and the silane coupling agent on the filler surface. This can dissipate energy through the sliding friction of molecular chains and maintain the resilience through the mechanical interlocking of molecular chains, thereby achieving high damping and high resilience of the organosilicon thermal conductive gel.

[0120] Table 1

[0121]

[0122]

[0123] Example 1

[0124] The thermally conductive gel and copper plate from Example 1 were arranged in a copper plate-thermally conductive gel-copper plate sandwich structure, and then a laminate with a thermally conductive gel thickness of 1 mm was obtained under the action of a press.

[0125] Comparison of effects 1-2:

[0126] Similar to Example 1, the thermally conductive gel in Comparative Examples 1-2 was further prepared to obtain a laminate with a copper plate-thermally conductive gel-copper plate sandwich structure.

[0127] To verify the feasibility of the thermally conductive gel prepared in this invention as a thermal interface material, a laminate was prepared using the thermally conductive gels prepared in the examples and comparative examples. After undergoing 40 compression-recovery cycles at a high strain of 20%, the adhesion between the copper plate and the thermally conductive gel interface was observed using an ultrasonic microscope. Figures 3-5 As shown, the gray area represents good interfacial adhesion between the copper plate and the thermally conductive gel, while the black area represents voids formed due to interfacial delamination between the copper plate and the thermally conductive gel. The interfacial adhesion stability is defined by the ratio of the area of ​​the gray area to the area of ​​the dark area, thus illustrating the ability of resilience to maintain the heat dissipation stability of the thermally conductive gel. The results show that the laminate in Example 1, using a thermally conductive gel with excellent resilience (Example 1), better maintains the stability of the interfacial adhesion area (e.g., ...). Figure 3 As shown, the interfacial bonding area remained at 84% after 40 compression-recovery cycles, which is significantly better than Comparative Example 1 (the thermal conductive gel in Comparative Example 1). Figure 4 ) and Comparative Example 2 (the thermally conductive gel in Comparative Example 2, Figure 5 This will effectively ensure the heat dissipation effect of the system. Therefore, the organosilicon thermally conductive gel prepared by this invention, which combines high damping, high resilience, and high thermal conductivity, can be used as a thermal interface material. Its excellent damping and resilience properties can ensure the heat dissipation stability in practical applications, and will work in conjunction with its high thermal conductivity to ensure the operational stability of the device and extend its service life.

[0128] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A thermally conductive gel possessing both high damping and high resilience properties, characterized in that, By weight, it includes: (1) 1-70 parts of side-chain vinyl silicone oil; (2) 0.1~20 parts of double-ended hydrogen-containing silicone oil; (3) 0.01~5 parts of hydrogen-containing silicone oil in the side chain; (4) 1-10 parts of single-ended hydrogen-containing silicone oil; (5) Catalyst 0.01~1.0 parts; (6) Inhibitor 0.005~0.5 parts; (7) 80-95 parts of modified thermally conductive filler; The modified thermally conductive filler is a thermally conductive filler modified with a silane coupling agent; the mass of the silane coupling agent is 0.5% of the mass of the thermally conductive filler; the hydrogen content of the single-ended hydrogen-containing silicone oil is 0.01%~0.12%; The silane coupling agent is selected from at least one of 3-(polysiloxane)propyltrimethoxysilanes shown in formula (1); (1) n=3 or 6.

2. The thermally conductive gel according to claim 1, characterized in that, The thermally conductive gel comprises, by weight: (1) 6-10 parts of side-chain vinyl silicone oil; (2) 0.1~1 parts of double-ended hydrogen-containing silicone oil; (3) 0.01~0.03 parts of hydrogen-containing silicone oil in the side chain; (4) 1-4 parts of single-ended hydrogen-containing silicone oil; (5) Catalyst 0.01~1.0 parts; (6) Inhibitor 0.005~0.5 parts; (7) 80-95 parts of modified thermally conductive filler.

3. The thermally conductive gel according to claim 1, characterized in that, The preparation method of the modified thermally conductive filler includes the following steps: The modified thermally conductive filler is obtained by dispersing the thermally conductive filler in a hydrolysate containing the silane coupling agent and stirring the mixture.

4. The thermally conductive gel according to claim 3, characterized in that, The stirring reaction is carried out at room temperature for 0.5 to 2 hours, followed by a reaction at 100 to 150°C for 0.5 to 2 hours.

5. The thermally conductive gel according to claim 3, characterized in that, The hydrolysate containing the silane coupling agent is a mixed solution containing the silane coupling agent, a first solvent, and a second solvent; the first solvent is selected from at least one of water and toluene; and the second solvent is selected from at least one of ethanol and methanol.

6. The thermally conductive gel according to claim 5, characterized in that, The mass ratio of the silane coupling agent, the first solvent, and the second solvent is 1:0.5~2:1~5.

7. The thermally conductive gel according to claim 5, characterized in that, The method for preparing the hydrolysate containing the silane coupling agent includes mixing and stirring the silane coupling agent, a first solvent, and a second solvent until the solution becomes clear.

8. The thermally conductive gel according to claim 1, characterized in that, The catalyst is selected from at least one of chloroplatinic acid, chloroplatinic acid-isopropanol complex, and chloroplatinic acid-divinyltetramethyldisiloxane complex.

9. The thermally conductive gel according to claim 1, characterized in that, The inhibitor is selected from at least one of ethynylcyclohexanol, 2-phenyl-3-butyn-2-ol, 2-methyl-3-butyn-2-ol, 3-methyl-1-ethynyl-3-ol, 3,5-dimethyl-1-ethynyl-3-ol, and 3-methyl-1-dodecynyl-3-ol.

10. The thermally conductive gel according to claim 1, characterized in that, The thermally conductive filler is selected from at least one of alumina, aluminum, zinc oxide, aluminum hydroxide, and magnesium hydroxide.

11. The thermally conductive gel according to claim 1, characterized in that, The particle size of the thermally conductive filler is 0.1~100 μm.

12. The thermally conductive gel according to claim 1, characterized in that, The thermally conductive filler is formulated in a mass ratio of 40~60:40~60:1~30, with a particle size of 80~100 μm: 20~50 μm: 0.1~10 μm.

13. A method for preparing the thermally conductive gel according to any one of claims 1-12, characterized in that, Includes the following steps: (1) Stir the side-chain vinyl silicone oil, double-ended hydrogen-containing silicone oil, side-chain hydrogen-containing silicone oil, single-ended hydrogen-containing silicone oil, inhibitor and modified thermally conductive filler; (2) After adding the catalyst, continue stirring to obtain the thermally conductive gel.

14. The preparation method according to claim 13, characterized in that, In step (1), the stirring is carried out under vacuum conditions.

15. The preparation method according to claim 14, characterized in that, The vacuum level is not lower than -90.0 kPa.

16. The preparation method according to claim 13, characterized in that, The stirring speed is 50~100 rpm, and the stirring time is 1~3 h.

17. The preparation method according to claim 13, characterized in that, In step (2), the continued stirring is carried out under vacuum conditions.

18. The preparation method according to claim 17, characterized in that, The vacuum level is not lower than -90.0 kPa.

19. The preparation method according to claim 13, characterized in that, The stirring speed is 50-100 rpm, and the stirring time is 1-3 h.

Citation Information

Patent Citations

  • High-hysteresis thermal interface material as well as preparation method and application thereof

    CN113527893A

  • A drop-resistant thermally conductive gel and its preparation method, electronic instruments

    CN113755015B

  • Low-hysteresis heat-conducting gel and preparation method thereof

    CN114031944A

  • Heat-conducting gel with high heat-conducting and damping functions as well as preparation method and application of heat-conducting gel

    CN114163818A

  • Wideband wide-temperature-range high-damping heat-conducting gel as well as preparation method and application thereof

    CN114479476A